Determinants of Malaysia halal brand equity / Ahmad Mazlan Ahmad Shamshudin - Ahmad Shamshudin, Ahmad Mazlan (2008)
The purpose of this paper is to investigate the determinant of 'halal' brand equity in Malaysia. 195 respondents participated in the survey. 18 questions on a seven-item Likert scale were used and 8 questions on demographic profiles were asked. SEM was used to analyze the results. The results showed that Muslim consumers only perceived that brand loyalty as the determinant of brand equity. However, brand awareness and perceived quality also contributed to the brand equity but were not significant. The results have significant implications: the fact that only brand loyalty gives significant effect to brand equity when 'halal' food product is concerned. This should trigger marketing managers' priorities when designing their marketing strategy to market 'halal' food products.